Hamba Tuhan dan Tuan: Pemikiran Teologis Menurut Kesetaraan Status Dalam Justifikasi Allah - Desima Djumetan (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
The Book of Philemon describes a slave named Onesimus who ran away from his master, Philemon (a rich man). It is possible that Onesimus took away money or valuables (18-19) or in another narrative Onesimus left his master's house dishonorably or an act that should not have been tolerated by Philemon who was a servant of God, who did not compromise with sin after experiencing repentance. Indirectly, the Apostle Paul asked Philemon not to demand compensation in any form by showing himself as the person responsible for what Onesimus had experienced. Was the Apostle Paul on the side of evil or was it because the Apostle Paul had arrested Onesimus in the Gospel of Christ? because at that time the escape of a slave was a crime and was a major highlight. There were even soldiers specifically designated to chase down the escapees. Slaves who did not have a hiding place or protection usually ran to big cities and hid among the crowds of people in the city. This was a threat to slaves not to live as they pleased with their masters. This research aims to get answers about the condition or fate of slaves who have wronged their masters and the new status for slaves after being found in a fatal error. The contents of the book contain a solid and high-quality message. In this research the author used the (library) method or library search. The Apostle Paul softened Philemon's request, because as fellow servants God must love all sinners and release forgiveness by being together at home and being part of God's family who trust each other. Servants of God are given God's authority to share the gospel of Christ.